Copper oxide resistive switching memory for e-textile - Jin-Woo Han; M. Meyyappan (AIP Advances, 2011)
A resistive switching memory suitable for integration into textiles is demonstrated on a copper wire network. Starting from copper wires, a Cu/CuxO/Pt sandwich structure is fabricated. The active oxide film is produced by simple thermal oxidation of Cu in atmospheric ambient. The devices display a resistance switching ratio of 102 between the high and low resistance states. The memory states are reversible and retained over 107 seconds, with the states remaining nondestructive after multiple read operations. The presented device on the wire network can potentially offer a memory for integration into smart textile.